Microeconomics and behavior - Frank, Robert H. (New York McGraw-Hill Book Company, 2006)
Publisher description from Library of Congress: "Robert Frank's Microeconomics and Behavior covers the essential topics of microeconomics while exploring the relationship between economics analysis and human behavior. The book's clear narrative appeals to students, and its numerous examples help students develop economic intuition. This book introduces modern topics not often found in intermediate textbooks. Its focus throughout is to develop a student's capacity to "think like an economist."
Part 1: Introduction --
Part 2: The Theory of consumer behavior --
Part 3: The Theory of the firm and market structure --
Part 4: Factor markets --
Part 5:. General equilibrium and welfare --
Includes bibliographical references & index
Keywords: Microeconomics; MICROECONOMICS; CONSUMER BEHAVIOUR